Disrupting the Present: An Autobiographical Narrative of Educational Angst - Alyson Hoy Price (Canadian Society for Studies in Education, 2008)
This paper offers a narrative account of my 'journey' in graduate studies and was first presented at the University of British Columbia's Faculty of Education's Annual Graduate Student Retreat in February 2008. Examining the gap that exists between the time of one's experience in education and the time of narrating that experience, this paper questions whether those of us who inhabit a place called higher education can claim to know what education is. It offers a means for thinking through the complexities and the 'queerness' of the time of education through personal journal reflections that highlight the shifting relations between past and present, and that hold tight the tensions which exist between the processes of reconstruction, interpretation, and narration.